Reverse encoding distortion correction for diffusion-weighted MRI: Efficacy for improving image quality and ADC evaluation for differentiating malignant from benign areas in suspected prostatic cancer patients. Issue 162 (May 2023) - Ueda, Takahiro; Ohno, Yoshiharu; Shinohara, Maiko; Yamamoto, Kaori; Ikedo, Masato; Yui, Masao; Yoshikawa, Takeshi; Takenaka, Daisuke; Ishida, Sayuri; Furuta, Minami; Matsuyama, Takahiro; Nagata, Hiroyuki; et al.
Highlights: Signal-to-noise ratio (SNR) of reverse encoding distortion correction diffusion-weighted imaging (RDC DWI) was significantly higher than that of DWI alone (p < 0.05). Apparent diffusion coefficients (ADCs) of malignant prostatic lesions on RDC DWI and DWI were significantly lower than those of benign prostatic lesions on RDC DWI and DWI (p < 0.05). When feasible threshold values were applied, specificity (SP) and accuracy (AC) of RDC DWI (SP: 72.1%, AC: 79.1%) were significantly higher than those of DWI (SP: 64.0%, p < 0.05; AC: 74.4%, p < 0.05). Abstract: Purpose: The purpose of this study was to determine the influence of reverse encoding distortion correction (RDC) on ADC measurement and its efficacy for improving image quality and diagnostic performance for differentiating malignant from benign prostatic areas on prostatic DWI. Methods: Forty suspected prostatic cancer patients underwent DWI with or without RDC (i.e. RDC DWI or DWI) using a 3 T MR system as well as pathological examinations. The pathological examination results indicated 86 areas were malignant while 86 out of 394 areas were computationally selected as benign. SNR for benign areas and muscle and ADCs for malignant and benign areas were determined by ROI measurements on each DWI. Moreover, overall image quality was assessed with a 5-point visual scoring system on each DWI. Paired t -test or Wilcoxon's signed rank test was performed to compare SNR and overall image quality for DWIs. ROC analysis was then used to compare the diagnostic performance, and sensitivity (SE), specificity (SP) and accuracy (AC) of ADC were compared between two DWI by means of McNemar's test. Results: SNR and overall image quality of RDC DWI showed significant improvements when compared with those of DWI (p < 0.05). Areas under the curve (AUC), SP and AC of DWI RDC DWI (AUC: 0.85, SP: 72.1%, AC: 79.1%) were significantly better than those of DWI (AUC: 0.79, p = 0.008; SP: 64%, p = 0.02; AC: 74.4%, p = 0.008). Conclusion: RDC technique has the potential to improve image quality and ability to differentiate malignant from benign prostatic areas on DWIs of suspected prostatic cancer patients.